2012
DOI: 10.4240/wjgs.v4.i7.171
|View full text |Cite
|
Sign up to set email alerts
|

Use of bovine pericardium graft for abdominal wall reconstruction in contaminated fields

Abstract: AIM:To employ, in such conditions, a biological graft such as bovine pericardium that offers resistance to infection. METHODS:In our surgical department, from January 2006 to June 2010, 48 patients underwent abdominal wall reconstruction using acellular bovine pericardium; of these 34 patients had a contaminated wound due to diffuse peritonitis (complicated diverticulitis, bowel perforation, intestinal infarction, strangled hernia, etc. ) and 14 patients had hernia relapse on infected synthetic mesh. RESULTS:I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Nevertheless, it may have a high rejection rate and adhesion to surrounding tissues, be more allergic, and be associated with calculi formation in patients undergoing urologic or vascular surgeries [8,61]. In contrast, BP has been demonstrated to be associated with no evidence of calcification, infection, thromboembolic events, or failure in pediatrics undergoing cardiac surgeries [62,63]. Additionally, it is deemed an appropriate graft in infected tissues [62].…”
Section: Pericardial Tissue Features and Feasibilitymentioning
confidence: 99%
“…Nevertheless, it may have a high rejection rate and adhesion to surrounding tissues, be more allergic, and be associated with calculi formation in patients undergoing urologic or vascular surgeries [8,61]. In contrast, BP has been demonstrated to be associated with no evidence of calcification, infection, thromboembolic events, or failure in pediatrics undergoing cardiac surgeries [62,63]. Additionally, it is deemed an appropriate graft in infected tissues [62].…”
Section: Pericardial Tissue Features and Feasibilitymentioning
confidence: 99%
“…It is a reliable substrate because of the effective mechanical support, biocompatibility with host tissues, and minimal tissue irritation. 7,8 Recent studies have examined the use of acellular bovine pericardium (ABP) grafts as a scaffold in pelvic floor reconstruction. 9 Human adipose-derived stem cells (hASCs) are a suitable option for reseeding, because it is convenient to harvest them in large quantities using minimally invasive techniques, and additionally, these MSCs maybe reduce the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine pericardium appears to have a lower complication rate (ranging between 3% and 10% in the studies examined [39][40][41] ) and recurrence rate (0%-19%) than other biologic mesh products ( in the field of AWR. A recent study of 120 patients who underwent a non-bridge inlay AWR with either porcine acellular dermal matrix (69 patients) or bovine acellular dermal matrix (51 patients) demonstrated significantly lower overall complication rates with bovine acellular dermal matrix (44.9% overall complications in the porcine acellular dermal matrix group versus 25.5% in the bovine acellular dermal matrix group).…”
Section: Bovine Pericardium and Dermal Meshmentioning
confidence: 99%
“…39 D'Ambra et al studied 48 contaminated abdominal wall repairs with bovine pericardium and found a recurrence rate of 8% and wound complication rate of 10% over a mean follow-up of 22 months. 40 A recent study by Gurrado et al demonstrated a 3% wound-infection rate and 0% recurrence rate in a study of contaminated incisional hernia repair with bovine pericardium. Gurrado et al compared the wound-infection and recurrence rates to contaminated incisional hernia repairs with synthetic mesh and suture repair alone and found that bovine pericardium was associated with significantly lower rates of both endpoints.…”
Section: Bovine Pericardium and Dermal Meshmentioning
confidence: 99%